PENGARUH EFEKTIFITAS IKLAN DAN CITRA MEREK TERHADAP MINAT BELI SEPEDA MOTOR YAMAHA THAMRIN (Studi pada Service Center Yamaha Thamrin Semarang, Jawa Tengah) - Samiaji Wicaksono, 14.05.51.0208; Sutejo, Bambang (Students' Journal of Economic and Management, 2019)
This study aims to analyze the effect of advertising effectiveness and brand image on the interest in buying a Yamaha Tamrin Semarang bike. The population in this study were consumers who bought a Yamaha montor bike at Yamaha Tamrin Semarng. The number of samples used in this study were 100 people. Data collection is done by questionnaire with purposive sampling technique. The data analysis technique used is multiple linear regression analysis to determine the effect of variable advertising effectiveness and brand image on the interest in buying a Yamaha Tamrin Semarang bike. The results showed that (1) advertising effectiveness had a positive and significant effect on buying interest (2) brand image had a positive and significant effect on the interest in buying a Yamaha bicycle bike.